Faktor Faktor Yang Mempengaruhi Minat Mahasiswa Vokasi Akuntansi Untuk Bekerja Di Bidang Perpajakan - Efendi, Alfarisi; Septi Purwaningsih; Baiq Solatiyah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This study aims to determine the effect of financial rewards, job market considerations, and job perceptions on the interest of vocational accounting students who have taken taxation courses to work in the field of taxation. This analysis uses independent variables, namely financial rewards, job market considerations, and perceptions. The dependent variable is interest, and the sample used in this study consists of accounting students who have completed taxation courses. The sampling technique used is snowball sampling. The number of respondents whose data can be processed is 113 students, and the data will be processed using SPSS statistics. This study shows that financial rewards and job market considerations have a significant effect on the interest of vocational accounting students to pursue a career in taxation, with a significance value of 0.000 (<0.05) each. Meanwhile, perception does not have a significant effect because it has a significance value of 0.181 (> 0.05). This finding confirms that financial factors and job market opportunities are the main considerations in students' career decisions in the field of taxation.